Mapping Iron Oxide Distribution on the Ground Surface of the Tugu Barat Oil and Gas Field Using Landsat 8 OLI and Field Data - Tri Muji Susantoro; Suliantara Suliantara; Ketut Wikantika; Asep Saepuloh; Agung Budi Harto; Herru Lastiadi Setiawan; Fitriani Agustin; Adis Jayati; Kurdianto Kurdianto; Sayidah Sulma; Sukristiyanti Sukristiyanti (Scientific Contributions Oil and Gas, 2024)
Previous studies have demonstrated that Landsat series data can be utilized to map rock change in arid and semi-arid environments. In this study, Landsat 8 Operational Land Imager (OLI) was used to map the presence of iron oxide (ferrous, ferric, and hematite) in the topsoil of the Tugu Barat Oil and Gas Field, Northwest Java Basin, Indonesia. The aim is to map the distribution of iron oxide and analyze it for detection of the presence of microseepage. The results show that the concentration of the mineral hematite indicates an anomaly, where the edge of the field is very low and tends to rise in the middle, but this condition is unclear, because of the presence of red soil containing high hematite in the north. Based on analysis indicates an anomaly, where the edge of the field is very low and tends to rise in the middle, but this condition is unclear, because of the presence of red soil containing high hematite in the north. Based on analysis of Landsat 8 OLI data, ferrous oxide concentrations show an increase at the edge of the field, especially in the southeast. However, this condition is less visible in the west because of the high vegetation density. The ferric oxide concentration shows the opposite pattern to the ferrous oxide concentration. These results are supported by the ferrous oxide index results from soil reflectance spectra recorded using Analytical Spectral Devices (ASD). Where the ferrous oxide concentration is low at the edge then tends to rise in the middle of the field. Meanwhile, the analysis of ferric oxide from the spectral reflectance of soil from ASD results does not show clear differences. The Normalized Iron Oxide Difference Index (NIODI) analysis shows the presence of small amounts of hematite and no geotite. The research results show evidence of microseepage indications at the edge of the field, especially at the southeastern edge. Iron oxide mapping has the potential to support oil and gas exploration through analysis of alteration processes which are thought to be the impact of micro-seepage.